Avaliações reprodutivas em três linhagens de tilápias do Nilo (Oreochromis niloticus) cultivadas no Brasil - Almeida, Diones Bender (2012)
The Nile tilapia (Oreochromis niloticus) is one of the most significant species of the current fish farming. All knowledge related to the reproductive behavior of this species is important for defining some selection criteria as well as a better understanding of their reproductive characteristics. Therefore, this research aimed to evaluate the spermatic characteristics of the semen, together with the reproductive acting of females of three different strains of Nile tilapia (Supreme, Premium Aquabel and Chitralada). These evaluations are necessary before establishing genetic breeding program for the species, in order to determine what kind of selection criteria will be used. The collections of data related to the reproducers of both sexes were taken in the Aquabel Pisciculture Station, located in Rolândia/PR. Thirty males were used in the seminal evaluation and seventy five females in the reproductive evaluation of each strain. The reproduction of the females was observed for seven weeks through weekly collections. It was evaluated parameters as volume of eggs/spawing, number and weight of eggs/female, number of eggs/Kg of fish, hatching rates, percentage of females that had not spawned, porcentage of spawning/week, more than two spawning during the seven weeks, average of the spawnings in chronological order and the frequency of spawnings. Of the evaluated strains, the PA presented higher averages for all of the parameters morfometrics and for great majority of the appraised reproductive parameters. As the male influence is as important as for the female in the reproductive process, it was aimed to identify by certain variables, productive and reproductive indexes in the semen that could be selected. Among them it can be mentioned the pH, semen collection, velocity and type of movement, motility, concentration, spermatic viability and integrity of membrane, mitochondrial and DNA. Looking for to identify the line to gather the largest number of desirable characteristics for cultivation, SUP is highlighted by presenting better results for great majority of these parameters. All these variables, for both males and females, are fundamental because in the fertilization process it is necessary that they have good quality. After the choice of these variables it would be possible to identify, among the worked strains, the more appropriate ones for the implantation of a future genetic breeding program.